The Role of Family in Preventing Bullying - Cumbuan Putri , Devin (Journal Corner of Education, Linguistics, and Literature, 2024)
Bullying is a form of violence intended to harm someone, carried out deliberately and repeatedly by an individual or group with more power over an individual or group that is weaker. The family plays a very important role in preventing bullying behavior. This article aims to explain the role of the family in preventing bullying in order to create an environment that supports the growth and development of children free from bullying behavior. This research uses a qualitative approach with a type of library research. The data sources in this study are secondary data obtained by collecting national and international journals. The data collection technique in this research involves a literature review process by stating the research objectives and then searching for journals relevant to the research objectives. The research results show that a family's understanding of bullying, the formation of values, positive parenting patterns, good role models and a conducive environment can prevent children from becoming victims or perpetrators of bullying. Bullying is an unlawful act. Many countries have passed laws prohibiting all forms of bullying, both in schools and in the workplace. This shows that bullying is not only considered a moral problem, but also a legal violation that must be prosecuted. Bullying is a negative behavior because of its destructive impact on the victim. The family plays a very important role in preventing bullying behavior. Several factors can prevent bullying, namely the family's understanding of bullying, the formation of positive values, positive parenting patterns, good role models, and a conducive environment. In other words, a family environment that supports and provides appropriate education can prevent children from becoming victims or perpetrators of bullying.